A qualitative study of dominance, jealousy and wives aggression - Edalati, Ali; Redzuan, Ma’rof; Mansor, Mariani; Abu Talib, Mansor (EuroJournals Publishing, 2009)
This paper examines qualitatively the relationship between dominance, jealousy and wives aggression. The study involved ten women (wives) who were already registered as “aggressive women” in counselling clinics, whom suffered from aggression (physical and psychological). Data collection technique employed in-depth interview. The results revealed that the women have pointed out three main factors of their aggressive behaviours- male dominance, sensitive to their husbands' relationship with other women, and sensitive to their husbands' relationship with their mother in law.